Knowledge level regarding Risk Factors of Acanthamoeba Keratitis in Contact Lens Users and the Relation to Student Characteristics of Faculty Medicine of University of Sumatera Utara - Subrata, Harith Naufal; Darlan, Dewi Masyithah (Buletin Farmatera, 2021)
Acanthamoeba Keratitisis an infection of cornea caused by one of free living amoeba group,Acanthamoeba spp. The most common risk factor ofAcanthamoeba Keratitisis the usage of contact lens. The purpose of this study is to assess knowledge level regarding risk factor forAcanthamoeba keratitisin contact lens users and its relation to student characteristics in Faculty Medicine of University of Sumatera Utara (FMUSU). This study is an analytical study withcross sectionaldesign. Data collection method was carried out by a questionnaire based survey. The study sample was selected by stratified proportional sampling method from FMUSU students with entry year of 2017-2020 that meets study criteria. Number of respondents of this study is 100 students. Univariate analysis showed knowledge level of respondents are 63% high, 34% medium, and 3% low. Bivariate analysis with Fishers Exact test showed there is no significant relation between sex with knowledge level regarding risk factor forAcanthamoeba Keratitisin contact lens users (C:0,068, X2:0,559, p:0,873) and there is significant relation between entry year with knowledge level regarding risk factor forAcanthamoeba Keratitisin contact lens users (C:0,312, X2:10,372, p:0,002).